Edukasi Literasi Media sebagai Upaya Pencegahan Hoaks di Era Digital pada Anggota Yayasan Roemah Tawon Kota Tangerang - Gultom, Parsaoran; Fairuz, Fara Dilla; Syaifuddin, Syaifuddin (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of Information and Communication Technology has changed the way people communicate and receive information, making the spread of hoaxes easier. Low awareness of fact-checking, particularly among individuals with high levels of social media use, poses a challenge to digital media literacy. This condition is also found among members of the Roemah Tawon Foundation, who have a limited understanding of media literacy in the digital era. This community service activity aims to enhance media literacy by improving participants' ability to distinguish between hoax and valid information. The activity was implemented through socialization or counseling using an interactive lecture approach. The target participants were housewives and elementary and secondary school students who are members of the Roemah Tawon Foundation in Tangerang city. The results indicate an increase in participants’ understanding of how to differentiate between hoax and valid information, as demonstrated by their ability to answer questions and actively engage in discussions. This improvement is expected to foster greater awareness in applying the 3C principle (check, compare, and confirm) before sharing information.